2019
DOI: 10.1007/s11069-019-03653-w
|View full text |Cite
|
Sign up to set email alerts
|

Climate impacts: temperature and electricity consumption

Abstract: One of the aspects of climate change is temperature rise. Temperature rise or fluctuations affect human economic activities and electricity consumption. This paper estimates the changes in electricity consumption due to temperature fluctuation at the county scale in rural China. By using the statistics of counties from 2006 to 2015 in a fixed-effect panel model, the results indicate that a one-degree temperature increase in summer days may lead to 0.015% more electricity consumption per capita, and this correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…One study conducted on the electricity demand of China explored the relation by dividing the sample into two groups, south and north, which explained the effect of the temperature in different topologies. The results showed that the load increased by 0.002% for every one-degree decrease in temperature for the southern region, whereas the load in the north region tended to use 0.021% more electricity than the southern region with every one-degree increase in temperature [26]. For the load dataset of Thailand, the variation was discussed in terms of hours.…”
Section: Temperature Effectmentioning
confidence: 97%
“…One study conducted on the electricity demand of China explored the relation by dividing the sample into two groups, south and north, which explained the effect of the temperature in different topologies. The results showed that the load increased by 0.002% for every one-degree decrease in temperature for the southern region, whereas the load in the north region tended to use 0.021% more electricity than the southern region with every one-degree increase in temperature [26]. For the load dataset of Thailand, the variation was discussed in terms of hours.…”
Section: Temperature Effectmentioning
confidence: 97%
“…Linear model schematic of the relationship between temperature and electricity consumption. (2) ...where d is the number of days in the research scale, T bn represents the balance point for space heating, T i represents the daily average temperature on day i, and T bc represents the balance point for space cooling.…”
Section: Climatic Variables Selection and Processingmentioning
confidence: 99%
“…The electricity supply chain is very sensitive to climate variability [1]. Rising temperatures associated with global warming are likely to lead to an increase in electricity consumption during periods when air conditioning is required [2]. It has been suggested that the impacts of climate change on the electricity sector may account for the majority of economic damages by the end of the century [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the works are focused on a particularly geographic area such as urban [8,25], tropical areas [14], cold places [15]; or countries such as the U.K. [10], the Netherlands [11], India [14], Russia [15], Thailand [16,17], Qatar [19], Portugal [20], Cyprus [21], the U.S.A. [22], China [23,25], South Korea [29]; or specific places such as Los Angeles [22], Nanjing [23].…”
Section: Related Workmentioning
confidence: 99%